KAJIAN NIRA AREN (Arenga pinnata MERR.) SEBAGAI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN TANAMAN PADI - saiful Darman; imam Wahyudi; Ramlan Ramlan (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
The objective of the research was to determine the effect of liquid organic fertilizer (LOF) made from arenga palm sap on the growth of wetland rice.  The research was conducted in the experimental plot of BPTP Sidondo Palu. The research results showed that the liquid organic fertilizer has significant effect on plant height at 28 days after planting (DAP).  The addition of 50 ml LOF L-1 resulted in significantly higher plant height (84.11 cm) than other concentrations at 5% level of Honestly Significant Test.  The LOF also has significant effect on number of tillers.  At 28 DAP, the addition of 25 ml LOF L-1 shows significanltly larger tiller number (17.97) than other concentrations while at 43 DAP, that of 50 ml L-1 has significantly highest tiller number (18.37). Meanwhile, the rice description of Mekongga variety indicates that it can produce 16 tillers. Key words:  Arenga palm sap, liquid organic fertilizer.